Importance of Functional Loss of FUS in FTLD/ALS - Ishigaki, Shinsuke; Sobue, Gen (Frontiers in Molecular Biosciences, 2018)
Fused in sarcoma (FUS) is an RNA binding protein that regulates RNA metabolism including alternative splicing, transcription, and RNA transportation. FUS is genetically and pathologically involved in frontotemporal lobar degeneration (FTLD)/ amyotrophic lateral sclerosis (ALS). Multiple lines of evidence across diverse models suggest that functional loss of FUS can lead to neuronal dysfunction and/or neuronal cell death. Loss of FUS in the nucleus can impair alternative splicing and/or transcription, whereas dysfunction of FUS in the cytoplasm, especially in the dendritic spines of neurons, can cause mRNA destabilization. Alternative splicing of the MAPT gene at exon 10, which generates 4-repeat Tau (4R-Tau) and 3-repeat Tau (3R-Tau), is one of the most impactful targets regulated by FUS. Additionally, loss of FUS function can affect dendritic spine maturations by destabilizing mRNAs such as Glutamate receptor 1 (GluA1), a major AMPA receptor, and Synaptic Ras GTPase-activating protein 1 (SynGAP1). Moreover, FUS is involved in axonal transport and morphological maintenance of neurons. These findings indicate that a biological link between loss of FUS function, Tau isoform alteration, aberrant post-synaptic function, and phenotypic expression might lead to the sequential cascade culminating in FTLD. Thus, to facilitate development of early disease markers and/or therapeutic targets of FTLD/ALS it is critical that the functions of FUS and its downstream pathways are unraveled.